Polycrystal CuO Curved Nanowires with Photocatalytic Antibacterial for Highly Sensitive Photoelectrochemical Detection of Ultralow-Concentration Ethanol in Solution. Issue 12 (16th December 2021) - Liang, Xu; Han, Lu; Gong, Pengwei; Zhu, Sicong; Huang, Ruibin; Chen, Rongsheng; Ni, Hongwei; Zhan, Weiting
Abstract : The polycrystal CuO curved nanowires on Cu mesh were synthesized by a facile alkalization method. This visible light-driven CuO curved nanowires were observed to have highly sensitivity for non-enzymatic ethanol sensing in solution and fast antibacterial property under flashlight irradiation. In order to reveal the mechanism of polycrystal CuO curved nanowires, the comparison between polycrystal CuO nanowires and single-crystal CuO nanowires were investigated based on the analysis of the morphology, nanostructure, theoretical modeling and photoelectrochemical performance. As a result, the highest photocurrent densities were obtained by polycrystal CuO curved nanowires, as the facet heterojunction in curved nanowires played a key role, which existed in the interface between facets CuO (111) and CuO (110) resulting in the effectively separation of photoelectron-holes, thereby increasing of the charge carrier density. Herein, the CuO curved nanowires were assembled as a photoelectrochemical sensor to detect the low concentration ethanol ranging from 10 to 100 nM, and then showed a highly sensitivity. The fast antibacterial performance of CuO curved nanowires was found to completely kill 10 7 CFU ml −1 E. coli under flashlight irradiation in 20 min. The proposed CuO curved nanowires electrode with self-cleaning performance can be ideal for monitoring the low concentration ethanol in real-time at room temperature as photoelectrodes.